Distributive justice in Islam : an expository study with special reference to zakah - Ansari, Abdul Haseeb (INSInet Publications, 2011)
During ignorance (jihalah) in Mecca, there existed unequal distribution of money. With the result of that wealth was concentrated in hands of elites, and the large section of the society was poor. Some of them were hardcore poor and were compelled to work as bonded labourers for the elites. As Islam believed in Islamic brotherhood (ukhuwwah), it came out with the scheme of trusteeship (amanah) and redistribution of money from haves to havenots. This message along with the message of oneness of God (tawheed) of Islam became disturbing to rich Meccans, as they wanted to maintain their supremacy over the poor mass. These became the reasons for them to oppose the Messenger of God (Prophet). Later, Islam came out with a mandatory system of zakah (also written as zakat) and compassionate voluntary payments as sadaqah, a pragmatic redistribution of resources, including money, which has now proven to be a competent mechanism for alleviation of poverty among Muslims around the world. From the contemporary practice in Muslim countries, it is proven that an institutionalized zakah system can faster implement this will of God in eradication of poverty. Even where it is not institutionalized like India or partially institutionalized, like Malaysia, it is being used as an instrument for alleviating poverty. The paper discusses various aspects of distributive justice in Islam with special reference to zakah, and concludes that an institutionalized or locally organized system of collection and distribution of zakah is a preferable choice.